Functional characterization of a eukaryotic melibiose transporter. - Lingner, Ulrike; Münch, Steffen; Sode, Björn; Deising, Holger B.; Sauer, Norbert (Plant Physiology, 2011)
Pathogenic fungi drastically affect plant health and cause significant losses in crop yield and quality. In spite of their impact, little is known about the carbon sources used by these fungi in planta and about the fungal transporters importing sugars from the plant-fungus interface. Here, we report on the identification and characterization of MELIBIOSE TRANSPORTER1 (MBT1) from the hemibiotrophic fungus Colletotrichum graminicola (teleomorph Glomerella graminicola), the causal agent of leaf anthracnose and stalk rot disease in maize (Zea mays). Functional characterization of the MBT1 protein in baker's yeast (Saccharomyces cerevisiae) expressing the MBT1 cDNA revealed that α-D-galactopyranosyl compounds such as melibiose, galactinol, and raffinose are substrates of MBT1, with melibiose most likely being the preferred substrate. α-D-glucopyranosyl disaccharides like trehalose, isomaltose, or maltose are also accepted by MBT1, although with lower affinities. The MBT1 gene shows low and comparable expression levels in axenically grown C. graminicola and upon infection of maize leaves both during the initial biotrophic development of the fungus and during the subsequent necrotrophic phase. Despite these low levels of MBT1 expression, the MBT1 protein allows efficient growth of C. graminicola on melibiose as sole carbon source in axenic cultures. Although Δmbt1 mutants are unable to grow on melibiose, they do not show virulence defects on maize.

Hexose transporters of a hemibiotrophic plant pathogen: functional variations and regulatory differences at different stages of infection. - Lingner, Ulrike; Münch, Steffen; Deising, Holger B.; Sauer, Norbert (Journal of Biological Chemistry, 2011)
Plant pathogenic fungi use a wide range of different strategies to gain access to the carbon sources of their host plants. The hemibiotrophic maize pathogen Colletotrichum graminicola (teleomorph Glomerella graminicola) colonizes its host plants, and, after a short biotrophic phase, switches to destructive, necrotrophic development. Here we present the identification of five hexose transporter genes from C. graminicola, CgHXT1 to CgHXT5, the functional characterization of the encoded proteins, and detailed expression studies for these genes during vegetative and pathogenic development. Whereas CgHXT4 is expressed under all conditions analyzed, transcript abundances of CgHXT1 and CgHXT3 are transiently up-regulated during the biotrophic phase, and CgHXT2 and CgHXT5 are expressed exclusively during necrotrophic development. Analyses of the encoded proteins characterized CgHXT5 as a low-affinity/high-capacity hexose transporter with a narrow substrate specificity for glucose and mannose. In contrast, CgHXT1 to CgHXT3 are high affinity/low capacity transporters that also accept other substrates, including fructose, galactose, or xylose. CgHXT4, the largest of the identified proteins, has only little transport activity and may function as a sugar sensor. Phylogenetic studies revealed hexose transporters closely related to the five CgHXT proteins also in other pathogenic fungi suggesting conserved functions of these proteins during fungal pathogenesis.

The hemibiotrophic lifestyle of Colletotrichum species - Muencha, Steffen; Lingner, Ulrike; Floss, Daniela S.; Ludwig, Nancy; Sauer, Norbert; Deising, Holger B. (Journal of Plant Physiology, 2008)
Colletotrichum species infect several economically important crop plants. To establish a compatible parasitic interaction, a specialized infection cell, the melanized appressorium, is differentiated on the cuticle of the host. After penetration, an infection vesicle and primary hyphae are formed. These structures do not kill the host cell and show some similarities with haustoria formed by powdery mildews and rust fungi. Therefore, this stage of infection is called biotrophic. Later in the infection process, necrotrophic secondary hyphae spread within and kill the host tissue. The lifestyle of Colletotrichum species is called hemibiotrophic, as biotrophic and necrotrophic developmental stages are sequentially established. As most Colletotrichum species are accessible to molecular techniques, genes can be identified and functionally characterized. Here we demonstrate that Agrobacterium tumefaciens-mediated transformation is a well-suited method for tagging of genes mediating compatibility in the Colletotrichum graminicola-maize interaction. © 2007 Elsevier GmbH. All rights reserved.
Keywords: Agrobacterium tumefaciens-mediated transformation; Anthracnose; Hemibiotrophy; Infection structures; Sugar transporters